2021
DOI: 10.1136/bmjopen-2021-054041
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre cohort study of cochlear implantation outcomes in Thailand

Abstract: ObjectivesTo report the status and outcomes of cochlear implantation in Thailand.DesignCohort study.SettingTertiary care and university hospitals.ParticipantsPatients who underwent cochlear implant surgery in Thailand.InterventionsThis project collected data from all government and university hospitals in Thailand where cochlear implant surgery was performed between 2016 and 2020.Primary and secondary outcome measuresBaseline characteristics, operation data, complications, audiological outcomes and quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The titles and abstracts of the remaining 1931 unique articles were screened, yielding 659 articles. Full‐text screening of these studies confirmed that 116 of these articles met the inclusion criteria 5,16‐130 . The selection process, including reasons for exclusion, is shown through a PRISMA flowchart in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The titles and abstracts of the remaining 1931 unique articles were screened, yielding 659 articles. Full‐text screening of these studies confirmed that 116 of these articles met the inclusion criteria 5,16‐130 . The selection process, including reasons for exclusion, is shown through a PRISMA flowchart in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, not enough comparable data were available to perform a meta-analysis (Tables 3 and 4) [1,15,16,54,55]. Although no age group was excluded from the literature review, it is apparent that there is limited data available regarding QoL surveys on children [1,[38][39][40][41][42]. This was one of the reasons why this study focused on collecting data from children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In children aged less than 5 years, the prevalence of hearing loss was 2% (7.5 million) and the incidence of permanent hearing loss in preschool children was 3.4 to 3.56 per 1000 [2][3][4][5]. Early detection and intervention can help to improve patients' quality of life [6].…”
Section: Introductionmentioning
confidence: 99%